Sudan : Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
This Statistical Appendix report on Sudan discusses economic indicators for the period 1994-2000. The report discusses gross domestic product; agricultural production; yield of cotton and noncotton crops; livestock production; manufacturing production; electricity tariff data; consumer and wholesale price indices; central government revenue and expenditure details; official exchange rates; analytical accounts of deposit money banks; monetary authorities' accounts; summary balance of payments; export and import data; loan disbursements; external public debt; and so on.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet